Does Knee Flexion Influence the Relationship between the Femoral Tunnel and the Lateral Anatomic Structures During ACL Reconstruction?. Issue 10 (October 2019) - Chung, Kwangho; Kim, Sung-Jae; Choi, Chong Hyuk; Kim, Sung-Hwan; Choi, Yunjong; Jung, Min
Abstract: Background: In ACL reconstruction, the relationship of the femoral tunnel outlet to the anatomy of the lateral knee is clinically important, but whether that relationship is influenced by knee flexion using a transportal technique is unclear. Questions/purposes: The purposes of this study were to (1) to describe the relationship between the outlet of the femoral tunnel and the lateral anatomic structures of the femur, including the lateral epicondyle, lateral collateral ligament, popliteus tendon, and lateral head of the gastrocnemius, as a function of knee flexion angle when the tunnel was created; and (2) to determine the knee flexion range of angles that best limits the risk of damage to these structures as the femoral tunnel is created during anatomic single-bundle ACL reconstruction using the transportal technique. Methods: Between January 2017 and June 2018, 113 patients underwent ACL reconstruction, of which 62 (55%) who had a primary single-bundle ACL reconstruction with transportal technique using autogenous quadruple hamstring graft were included. Patients who were treated with grafts other than autogenous quadruple hamstring tendon, and had concomitant ligamentous injury, revisional ACL reconstruction, previous operative history of the affected knee, osseous deformity and osteoarthritis were excluded. Included patients were divided into three groups according to their knee flexion angles as the femoral tunnel was created. The femoral tunnel was created with rigid straight reamer with the knee flexed as much as possible in figure-of-four position and the flexion angle was measured with a sterile 12-inch goniometer intraoperatively for all patients. Fourteen patients (23%) had the femoral tunnel created with the knee in < 120° of flexion, 23 (37%) had the tunnel created in 120° to 129° of flexion, and 25 (40%) had the tunnel created in ≥ 130° of flexion. The femoral tunnel's outlet and the lateral anatomic structures of the femur, including the femoral origins of the lateral epicondyle, lateral collateral ligament, popliteus tendon, and lateral head of the gastrocnemius, were identified on a three-dimensional model that was reconstructed using CT images taken on postoperative day 1. The shortest distances from the femoral tunnel's outlet to these lateral anatomic structures were measured by two observers and interobserver reliability was high (intraclass correlation coefficient > 0.75). The distances were compared among the groups, and a correlation analysis of the measured distances regarding the knee flexion angle during creation of the femoral tunnel was performed. The safe distance was set as 12 mm between the centers of the femoral tunnel's outlet and the lateral structures considering the footprint of the lateral structures, diameter of the femoral tunnel, and femoral tunnel widening. Any anatomic structures that were closer to the femoral tunnel than the safe distance were noted, and the cutoff point of knee flexion for injury to the lateral anatomic structures was determined with a receiver operating characteristic curve. Results: As knee flexion angle increased, the distance from the femoral tunnel to the lateral head of the gastrocnemius increased (r = 0.657, p < 0.001), and the distance to the lateral epicondyle decreased (r = -0.627, p < 0.001), as did the distance of the tunnel to the lateral collateral ligament (r = -0.443, p < 0.001) and the popliteus tendon (r = -0.653, p < 0.001). The cutoff point of the knee flexion angle associated with structural injury was 131° (sensitivity, 70%; specificity, 73%) for the lateral collateral ligament and 121° (sensitivity, 86%; specificity, 67%) for the lateral head of the gastrocnemius. Conclusions: As knee flexion increased, the femoral tunnel's outlet tended to move more anteriorly and distally. Consequently, the safe distance to the lateral head of the gastrocnemius increased and the distances to the lateral epicondyle, lateral collateral ligament, and popliteus tendon decreased with increased knee flexion. To avoid possible damage to the lateral anatomic structures and obtain stable fixation in ACL reconstruction using the transportal technique, we recommend creating a femoral tunnel within 121° and 131° of knee flexion. Level of Evidence: Level III, therapeutic study.